Wage Differentials: Trade Openness and Wage Bargaining - Gustavo Gonzaga; Beatriz Muriel; Cristina Terra (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
We build a theoretical model that incorporates unionization in the labor market into a Heckscher-Ohlin-Samuelson (HOS) framework to in- vestigate the impact of unionization on the Stolper-Samuelson Theorem. To capture the American economy case, we assume that unskilled labor in the manufactured goods sector is unionized, and that sector is intensive in skilled labor, and that trade liberalization increases the relative price of manufactured goods. In the HOS model, trade liberalization induces a reallocation of production towards the sector that uses intensively the country's most abundant factor. The resulting change in relative labor de- mand impacts wage bargaining in the unionized sector, which, in turn, has a dampening e ect on the Stolper-Samuelson e ect. Moreover, wages of unionized workers are even less responsive to trade liberalization. Through traditional mandated-wages regressions, we show that skilled-wage di er- entials changes were less pronounced among more unionized sectors in the U.S. economy for the 1979-1990 period.
Keywords: F16; J31; J51; 330; Stolper-Samuelson Theorem; wage bargaining; unionization